Mean score analysis on awareness of solid waste management in Malaysia - Zulkipli, Faridah; Mohd Nopiah, Zulkifli; Jamian, Nurul Husna; Ahmad Basri, Noor Ezlin; Cheng, Jack Kie (Human Resource Management Academic Research Society (HRMARS), 2022)
Solid waste management is a global issue impacted on climate changes and sustainable environment. Improper management would lead to highly generated amount of solid waste. These happened due to lack of an awareness of solid waste management among the citizen. Thus, this issue motivates the further investigation on awareness of solid waste management among citizens in Malaysia. The objectives are to identify the level of awareness, knowledge, practice, attitude and perception on solid waste management and to compare the level of awareness, knowledge, practice, attitude and perception on solid waste management by gender, age group and state regions. The scope of this study focused on citizens age above 18 years old. A sample of 422 respondents participated by answering the online questionnaire. The questionnaire is distributed using convenience sampling. A mean score analysis method is applied to analyze the results. The result show overall Malaysian citizens have a high level of awareness, knowledge, practice, attitude, and perception. Based on gender, age group and states region it shows slight differences in the level of awareness, knowledge, practice, attitude and perception among these categories. Hence, based on 422 respondents in 2022 show high awareness among the citizens in Malaysia. This result shows a positive contribution towards the 12th Malaysian Plan Agenda to focus on advancing sustainability to the environment by 2025 which aligned with sustainable development goals (SDGs).